2020
DOI: 10.1007/s00277-020-04138-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-driven endothelial damage: complement, HIF-1, and ABL2 are potential pathways of damage and targets for cure

Abstract: COVID-19 pandemia is a major health emergency causing hundreds of deaths worldwide. The high reported morbidity has been related to hypoxia and inflammation leading to endothelial dysfunction and aberrant coagulation in small and large vessels. This review addresses some of the pathways leading to endothelial derangement, such as complement, HIF-1α, and ABL tyrosine kinases. This review also highlights potential targets for prevention and therapy of COVID-19-related organ damage and discusses the role of marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
105
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 85 publications
3
105
0
6
Order By: Relevance
“…Troponin elevation three times the upper reference limit is known to be associated with worse in-hospital outcomes in COVID-19 patients 19,20 . It remains unclear whether the rise in cardiac biomarkers is related to viral myocarditis 5,6 or plaque rupture secondary to virus-induced inflammatory response [29][30][31] or a type 1 AMI. In this cohort of suspected type 1 myocardial infarction, there was a low prevalence of non-obstructive coronary disease and the angiographic characteristics and procedural management of the COVID-19 ACS were similar to the non COVID-19 ACS group.…”
Section: Discussionmentioning
confidence: 99%
“…Troponin elevation three times the upper reference limit is known to be associated with worse in-hospital outcomes in COVID-19 patients 19,20 . It remains unclear whether the rise in cardiac biomarkers is related to viral myocarditis 5,6 or plaque rupture secondary to virus-induced inflammatory response [29][30][31] or a type 1 AMI. In this cohort of suspected type 1 myocardial infarction, there was a low prevalence of non-obstructive coronary disease and the angiographic characteristics and procedural management of the COVID-19 ACS were similar to the non COVID-19 ACS group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the possible effect of the HIF-1α on the COVID-19 pathogenesis and ARDS symptoms in patients can be explained through its relevant role in other component of the immune system including the complement system [ 67 ]. According to previous studies, C3a and also C5a fractions of complement system have important roles in the pathogenesis of the infection related-lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with severe COVID-19 might experience cytokine release syndrome, and several of the cytokines involved in COVID-19 employ a distinct intracellular signaling pathway mediated by Janus kinases (JAKs), therefore, JAK inhibition presents an attractive therapeutic strategy for CRS [ 59 ]. What’s more, it has been reported that complement and HIF-1 are potential pathways of damage and targets for the cure of COVID-19-driven endothelial damage [ 60 ].…”
Section: Discussionmentioning
confidence: 99%